A Case Report on Moderate Depression as a Precipitating Factor for Chronic Gastritis - Rasyid, Rezza Dwi Ar; Ridlo, Fairuz; Karida, Rika Nur; Prisnidiawati, Ajeng; Basuki, Shinta Maulydiyah; Kasiani, Tutik Nur; Algristian, Hafid (Indonesian Scientific Publication, 2025)
Depression is increasingly acknowledged as a key contributor to gastrointestinal dysfunction, primarily through neuroendocrine mechanisms such as activation of the hypothalamic–pituitary–adrenal (HPA) axis. Elevated cortisol in depressive states may trigger increased gastric acid secretion, altered gut motility, and intestinal barrier disruption, which contribute to inflammation and recurrent gastritis. While chronic gastritis is often treated pharmacologically, the psychological dimension is frequently overlooked. This case report investigates the role of moderate depression as a triggering factor for chronic gastritis through HPA axis dysregulation. A 33-year-old woman diagnosed with both conditions was followed for six months. Data were obtained via DSM-5-based psychiatric assessments, medical records, and follow-up interviews. The patient was treated with sertraline (50 mg/day) and standard gastritis therapy. Notable improvements in depressive symptoms were observed, along with a marked reduction in gastritis recurrence. This outcome supports existing evidence that psychological stress can impact gastrointestinal health via neuroinflammatory responses, immune dysfunction, and microbiota alteration. The case highlights the importance of an integrated treatment model that addresses both psychological and physical aspects. Routine mental health screening in patients with persistent gastrointestinal symptoms may enhance treatment efficacy and reduce recurrence. A biopsychosomatic approach involving collaboration between psychiatry and gastroenterology is recommended for comprehensive and effective care.